Faktor-Faktor yang Menyebabkan Kejadian Stunting pada Balita di Wilayah Pesisir Desa Sorue Jaya Kecamatan Soropia Kabupaten Konawe - Nisrawati; Siti Hadrayanti Ananda H; Jenny Qlifianti Demmalewa; Abdurrakhman; Ellyani Abadi (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2022)
The prevalence of stunting in Sorue Jaya Village is higher than other villages and has increased, namely in 2019 there were 4.4% Stunting Toddlers and in 2020 it was 28.6%. This study aims to determine the factors that cause stunting in toddlers in the coastal area of ​​Sorue Jaya Village, Soropia District, Konawe Regency. This research is a correlational study with a cross sectional study design. The population is all toddlers in the coastal area of ​​Sorue Jaya Village, Soropia District, Konawe Regency as many as 86 people and a sample of 86 people obtained by total sampling. Stunting data was obtained by measuring height using microtoise and the variables of diet, exclusive breastfeeding, education, occupation, family income and number of family members were obtained by distributing questionnaires. Data were analyzed using chi-square test, fisher's exact and multiple longistic regression. The results showed that there was a relationship between a history of exclusive breastfeeding, feeding patterns, education, work and number of family members with the incidence of stunting in Toddlers in the Coastal Area of ​​Sorue Jaya Village, Soropia District, Konawe Regency with p value <0.05, and there was no relationship family income with the incidence of stunting with a p value of 1,000 > 0.05. The conclusion of this study is that the factors that cause stunting in the coastal area of ​​Sorue Jaya village are a history of exclusive breastfeeding, eating patterns, education, work and number of family members.